COSMN: Clustering-Based Optimization for 360-Degree Live Streaming over Mobile Networks: COSMN: Clustering-Based Optimization for 360-Degree Live Streaming over Mobile Networks - Nguyen Viet, Hung; Bui Huy, Hoang; Tran Thanh, Cong; Truong Thu, Huong (EAI Endorsed Transactions on Industrial Networks and Intelligent Systems, 2025)
The rapid growth of 360-degree video streaming has transformed how users experience immersive content, especially on mobile devices. However, delivering high-quality 360-degree video streams to mobile devices is challenging due to their constrained computational resources, limited bandwidth, and the need for real-time processing. The paper introduces COSMN (Clustering-Based Optimization for 360-Degree Video Streaming over Mobile Networks), an innovative framework to tackle these challenges. COSMN leverages a clustering-based optimization approach to dynamically adapt video streaming to the viewer’s region of interest (ROI), minimizing resource consumption while maintaining high-quality visuals for the most relevant portions of the video. The framework operates by dividing the 360-degree video into multiple tiles and clustering these tiles based on user viewing patterns. By predicting user behavior with clustering algorithms, COSMN efficiently prioritizes bandwidth and processing power for the tiles within the viewer’s ROI. The system also integrates adaptive bitrate streaming techniques to ensure seamless playback under varying network conditions. Experimental results demonstrate that COSMN significantly reduces bandwidth usage and computational load on mobile devices while providing a smooth and immersive viewing experience. Compared to traditional 360-degree online streaming methods, COSMN achieves superior performance in terms of latency, video quality, and resource efficiency. This work paves the way for scalable, 360-degree online streaming solutions on mobile platforms, making immersive video experiences more accessible and practical for everyday users.
Keywords: Mobile Network; Field Of View; 360-Degree Video; Clustering-Based Optimization; Quality of Experience; COSMN